Acne Vulgaris on the Upper Back and Chest Induced by Moisturizer Overuse: A Brief Review of a Case - Farnaz Azizi; Katie Sum; Nazanin Azizi; Howard I. Maibach (Dermato)
Acne vulgaris is a common skin condition often causing physical and emotional distress. We reported a case of 27-year-old female with rash and acne over the chest and upper back following continuous application of moisturizer. This case emphasizes the role of comedogenic moisturizers in acne development or worsening by disrupting the skin’s natural barrier, especially on oily areas including the chest and upper back. We aim to highlight an underrecognized but significant factor in developing acne vulgaris resulting in psychosocial impact and morbidity.